Comparative Study between Plastic and Metallic Stents for Biliary Decompression in Patients with Distal Biliary Obstruction. (6th September 2017) - Cabral, João Guilherme G.; Taglieri, Eloy; Pelosof, Adriane; Rosendo, Daniel; Ardengh, José Celso
Abstract : This paper presents a retrospective comparison of plastic versus metallic stents in the drainage of malignant distal biliary obstructions. We compared single plastic stents (SPS), multiple plastic stents (MPS), and metallic stents (SEMS) regarding clinical decrease of TB < 2.0 mg/dL, long-term patency, and adverse event. 58 patients (38 women) with MDBO were included. Diagnoses were 44 pancreatic adenocarcinoma (74.6%), 9 metastasis (15.5%), 3 pancreatic neuroendocrine tumors (5.1%), and 2 adenocarcinoma in the major papilla (3.4%). The number of patients included in the SPS, MPS, and SEMS was 17, 6, and 35, respectively. Comparing the survival curves with respect to obstruction, we observed a lower mean permeability of the SPS compared to that of the MPS with p < 0.003 and of the SEMS group (p < 0.01 ). There was no statistical difference between the use of MPS, despite the small number of patients compared to the use of SEMS (p < 0.13 ) to reach the satisfactory levels of bilirubin.